BIOSENSOR BASED ON CREATININE DEIMINASE AND рH-SENSITIVE FIELD-EFFECT TRANSISTOR FOR CREATININE ANALYSIS IN BLOOD SERUM - S. V. Marchenko (Biotechnologia Acta, 2013)
Creatinine is one of the most important analytes in up-to-date clinical analysis. Detection of this metabolite in different physiological body fluids is helpful for the estimation of kidney, muscle, and thyreoid disorders. Creatinine is a marker of renal glomerular filtration and is commonly considered as a diagnostic characteristic of the kidney function, the level of which should be controlled to assess the hemodialysis procedure. The experiments were carried out by potentiometric measuring method. A biosensitive element for creatinine detection was created on the basis of highly selective enzyme creatinine deiminase. The enzyme immobilization onto the surface of pH-sensitive field-effect transistor was performed using photopolymer. The creatinine deiminase-based bioselective element was developed. The main analytical characteristics of the developed biosensor were optimized, optimal conditions for the experiments with real samples were found. It was shown that biosensor based on creatinine deiminase is stable. The responses of biosensor were reproducible and liner range was from 0 to 2 mM with detection limit 0,02 mM. Quantitative determination of creatinine concentration in blood serum was elaborated; the data of biosensor measurement were compared with those obtained by the control method, high correlation was shown R = 0,96. A biosensor based on pH-sensitive field-effect transistor and immobilized creatinine deiminase, advantageous for its high sensitivity and selectivity, might be utilized for the quantitative evaluation of creatinine concentration in blood serum of the patients with renal failure as well as for monitoring hemodialysis efficiency.